2011
DOI: 10.1111/j.1744-6570.2010.01206.x
|View full text |Cite
|
Sign up to set email alerts
|

Doing Good, Feeling Good: Examining the Role of Organizational Citizenship Behaviors in Changing Mood

Abstract: This study investigates whether the altruism and courtesy dimensions of organizational citizenship behaviors (OCB) regulate mood at work. Social psychological theories of mood regulation suggest helping behaviors can improve individuals’ moods because helping others provides gratification and directs attention away from one's negative mood. We capture mood states prior to and following the enactment of OCBs using experience sampling methodology in a sample of managerial and professional employees over a 3‐week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
214
2
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(244 citation statements)
references
References 102 publications
11
214
2
6
Order By: Relevance
“…This is good news for organizations because motivation of employees is generally high and it is, therefore, easier to work on education and learning of such personnel. Most authors also agree that motivation rather than interpersonal relationships influence interpersonal circumstances (Day, Sin and Chen, 2004;Glomb, et al 2011). Almost the same results were achieved in relation to tangible rewards (rewards and benefits), as stated in the results of this article.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…This is good news for organizations because motivation of employees is generally high and it is, therefore, easier to work on education and learning of such personnel. Most authors also agree that motivation rather than interpersonal relationships influence interpersonal circumstances (Day, Sin and Chen, 2004;Glomb, et al 2011). Almost the same results were achieved in relation to tangible rewards (rewards and benefits), as stated in the results of this article.…”
Section: Discussionsupporting
confidence: 73%
“…The questions were designed based on theories and similar researches driven by Gannon and Maher (2012), Dalal, Bhave and Fiset (2014), Day, Sin and Chen (2004), Glomb, et al (2011), Vancouver (2012, Vancouver, Thompson and Williams (2001) and Sitzmann and Yeo (2013). Respondents' reactions to target statements and their attitudes to the given matter were restricted by offering a set of several statements.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has also reported various positive effects of helping behavior, particularly on personal development (Hansen, Larson & Dworkin, 2003) and physical and psychological well-being (Brown, Nesse, Vinokur & Smith, 2003;Sonnentag & Grant, 2012;Glomb, Bhave, Miner & Wall, 2011). Spitzmuller and Van Dyne (2013) distinguished between two streams of research on helping; first stream of research is based on social exchange theory that treats helping behavior as a reactive behavior while the second is based on the functional motives approach that treats helping as a proactive behavior.…”
Section: Helping Behavior and Supervisor Satisfactionmentioning
confidence: 99%
“…For instance, Moynihan et al (2015) pointed out that altruism improved SWB by replacing more negative mood, because it becomes more difficult to indulge in a negative mood like sadness, anger, or fear if a person is focused on offering help. Findings have shown that altruism can improve social relationships, raise gratification, and reduce negative emotions, and hence promote individuals' wellbeing (Bartlett & DeSteno, 2006;Glomb, Bhave, Miner, & Wall, 2011;Grant & Gino, 2010). Tian, Du, and Huebner (2015) revealed that altruistic behaviour was positively correlated with life satisfaction and positive affect.…”
Section: Internet Altruistic Behaviour and Subjective Wellbeingmentioning
confidence: 99%